Gender Representation in English as A Foreign Language (EFL) Textbooks for Senior High School in Indonesia - Puput Arfiandhani (Prominent, 2019)
English language textbooks, as one of the manifestations of language-in-education policy, played an important role to connect classroom language and real world language. The present study investigates the gender representation in the English as A Foreign Language (EFL) textbooks. The analysis is done by tallying the number of occurrence of male and female characters. The research results indicated that there is an equitable representation of both males and females. However, there is a gender bias portraying females. Males are portrayed to be more authoritative and put in the spotlight, such as the one of doing the networking in business meeting while female characters are in the background, doing presentation, giving speech, more representative in politics, in which females are absent on this spotlight.